Training Of Young Badminton Athletes With The Uniba Cup I Championship - Wawan Setiawan; Puji Setyaningsih; Lutfi Irawan Rahmat; Supono (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2020)
Badminton is in great demand by the community both as a daily sport and chosen to be a professional sport by many young Indonesians. It is proven by the large number of badminton athletes sprung up both at the regional and national level. All athletes involved in badminton have one goal, namely to make Indonesia famous in the world. With the slowness of the achievements of Indonesian athletes and to better maintain the competition of badminton achievements in the international arena, then we PGRI Banyuwangi University intends to hold a Badminton Championship SMA / SMK / MA throughout Besuki Raya